Influence of oxygen content and structural defects on low-temperature mechanical properties of high-temperature superconducting single crystals and ceramics - Lubenets, S. V.; Natsik, V. D.; Fomenko, L. S.; Kaufmann, H. -J.; Bobrov, V.S.; Izotov, A. N. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1997)
The data for the microhardness and fracture toughness of Y-Ba-Cu-O and Bi-based single crystals and ceramics in the temperature range 77-293 K are presented and analysed. Our study reveals that the microhardness of high temperature superconductors is very sensitive to the oxygen stoichiometry, the phase composition, the temperature, and to the microstructural defects such as impurities, intergranular boundaries, and voids. Attention is drawn to the anisotropy of the micromechanical properties and to the features of the fracture in the vicinity of the indentation. The data available on the plasticity of Y-Ba-Cu-O and Bi-Sr-Ca-Cu-O from micro- and macrotests are compared